2014
DOI: 10.5812/hepatmon.15275
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mutations Associated With Occult Hepatitis B Virus Status

Abstract: Context:Occult hepatitis B virus (HBV) status (OHBS) is simply defined as the presence of HBV DNA in the liver (with or without detectable HBV DNA in the serum), in the absence of serum HBV surface antigen (HBsAg). Importance of OHBS is mostly clinical, related to its possible role in spreading through blood transfusion and liver transplantation; causing classic forms of HBV. Mechanisms underlying this entity are poorly defined. Several possibilities have been suggested, with major classification into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The mutation in the stop codon was shown to associate with the HBeAg status [ 31 ]. Interestingly, this mutation has also proposed to be associated with the OBI status [ 32 , 33 ]. However, more studies are needed to warrant the role of W28* (G1896A) mutation in OBI development.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation in the stop codon was shown to associate with the HBeAg status [ 31 ]. Interestingly, this mutation has also proposed to be associated with the OBI status [ 32 , 33 ]. However, more studies are needed to warrant the role of W28* (G1896A) mutation in OBI development.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cryptic pathogenesis of OBI has been a major focus of research over the past three decades, with the most compelling viral molecular mechanism underlying the infection suggested to be mutations occurring within the viral HBsAg‐encoding gene and the overlapping polymerase (pol) gene frame . These OBI‐associated variations have been extensively investigated . However, a drawback to the majority of previous investigations has been the cross‐sectional study designs, resulting in a knowledge gap on the genetic stability of the variations over time.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] These OBI-associated variations have been extensively investigated. 15,19,20 However, a drawback to the majority of previous investigations has been the cross-sectional study designs, resulting in a knowledge gap on the genetic stability of the variations over time. The current study sought to investigate how the serologic and virologic course of OBI may evolve in a cohort of HIV co-infected patients before and during long term HBV-active HAART.…”
mentioning
confidence: 99%
“…Moreover, OBI diagnosis is possible by analyzing low levels of the harbored HBV-DNA (less than 200 IU/mL) by PCR, when HBsAg is absent ( 17 , 18 ). Several studies have shown that OBI increases the risk of HBV transmission through blood transfusion in hemodialysis patients ( 19 , 20 ); however, the prevention of OBI transmission in hemodialysis patients remains a challenge ( 21 ). There is notable variance in the prevalence of OBI in hemodialysis patients, ranging from 3.11% to 58%, worldwide ( 3 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%